Enrichment of Prebiotics in Foods Using Green Chemistry Approach - Arunrao Yadav, Supriya; V. Agte, Vaishali; S. Nilegaonkar, Smita (Current Organic Chemistry, 2014)
Prebiotics is an exciting concept in human nutrition and digestive function for which many physiological and health claims have already been made. There are only few oligosaccharides like inulin, trans galacto-oligosaccharides and lactulose which fulfil all the three strict criteria of prebiotics. The interest in the present prebiotic research has been to justify the health claims of new and unexplored experimental materials using these criteria for prebiotics. Most of the currently available prebiotics in the market are manufactured using chemical or synthetic approach. Synthetic oligosaccharides use chemical processing like isomerisation of lactose for lactulose, trans-galactosylation of lactose for trans-galactooligosaccharides and trans-fructosylation for production of oligofructose. Conversion of sucrose to fructose oligosaccharides is the frequently used method. The enzymes like β-glucosidases, β-galactosidases, β-fructosidase are used for hydrolysis of polysaccharides into oligosaccharides. Conversion of the normal starch to resistant nature is another approach for developing the prebiotics. Synthesis or sequential extractions of prebiotic involve processing of materials with various chemicals. The chemical waste materials of such processes are a big issue for disposal. Thus, use of current chemical approach for the oligosaccharide synthesis need to be reassessed and modified. This can be done using green chemistry approach maintaining the safety issues for health. There is a need of research for finding out better alternatives in production of prebiotics. Use of fruits and vegetables for multifunctional food supplements provides safe alternative for improving the health. Present paper attempts the critical review of reported studies on prebiotic development with an emphasis on green chemistry approaches.
Keywords: Fructans